2008
DOI: 10.1179/crn.2008.004
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sleep Bruxism and Temporomandibular Disorders: A Polysomnographic Pilot Study

Abstract: The aim of this study was to verify the association between sleep bruxism (SB) and temporomandibular disorders (TMD) in a sample of 14 TMD patients and 12 healthy control subjects. All participants were evaluated using a clinical questionnaire, visual analog scale (VAS) for TMJ/muscle palpation, and by functional examination. The experimental group was divided into three TMD subgroups: joint sounds and pain, muscular tenderness, and mixed diagnosis. All participants underwent polysomnographic recording (PSG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 18 publications
1
28
1
5
Order By: Relevance
“…The causes of TMD can therefore be described as multifactorial, including an association with SB [9,14]. It is important to note, however, that the association with SB has been a matter of controversy [42] for a long time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The causes of TMD can therefore be described as multifactorial, including an association with SB [9,14]. It is important to note, however, that the association with SB has been a matter of controversy [42] for a long time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of these studies were initially conducted for mechanistic reasons. It is interesting to note that although some of these studies identified an association between TMD and SB [11,12], others made no such connections [13][14][15]. These differences could be explained by heterogeneous study methodology and/ or the use of different clinical examination procedures to assess the presence of MP.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, further studies with gold standard diagnoses are necessary to determine whether the signs of pain in the muscles of the face upon awakening or following extensive talking or chewingare associated with bruxism 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is no surprise that those using the tautological ASDA definition to test a relation between SB the behaviour and facial pain (21) or between SB and tooth wear (22) occasionally find an association between SB and those health outcomes. It is actually startling to acknowledge that, given the definition with which the PSG-based RDC/SB is intended to maximise correspondence, only one study found an association between TMD status and RDC/SB (23), which was not apparent in an earlier subsample (24) and which found such high rates of SB in both case (63%) and control (33%) samples that either standards for SB or overall sample selection (or both) raise serious questions about research design. In contrast, multiple other studies have failed to find a relation between RDC/SB-diagnosed SB and TMD pain (3, 20, 2527).…”
Section: Introductionmentioning
confidence: 99%